Predictors of Significant Liver Fibrosis in People with Chronic Hepatitis C Who Inject Drugs in the Czech Republic - Sona Frankova; Nikola Uzlova; Dusan Merta; Veronika Pitova; Jan Sperl (Life, 2023)
Background and objectives: HCV infection often remains untreated in people who inject drugs (PWID), albeit they may present with advanced liver fibrosis at a young age. We aimed to assess the rate of patients with significant fibrosis in PWID starting anti-HCV therapy and identify the factors associated with severe fibrosis. Methods: The cohort of 200 patients was divided into two groups: F0–F2 (N = 154, 77%), patients with liver stiffness measurement (LSM) < 10.0 kPa, and F3–F4 (N = 46, 23%), with LSM ≥ 10.0 kPa, indicating significant liver fibrosis. Results: In group F3–F4, there were significantly more males, and the patients were older, with a higher BMI. The number of long-term abstaining patients was significantly higher in group F3–F4 compared with group F0–F2, as well as the proportion of patients reporting harmful drinking. Obesity (OR 4.77), long-term abstinence from illicit drugs (OR 4.06), harmful drinking (OR 2.83), and older age (OR 1.17) were significant predictors of advanced fibrosis in PWID starting anti-HCV therapy. Conclusions: A quarter of PWID presented with significant liver fibrosis at treatment initiation. Obesity, long-term drug abstinence, harmful drinking, and older age contributed to significant liver fibrosis.